Correction: Long term effectiveness of inactivated vaccine BBIBP-CorV (Vero Cells) against COVID-19 associated severe and critical hospitalization in Morocco. - Jihane Belayachi; Majdouline Obtel; Abdelkader Mhayi; Rachid Razine; Redouane Abouqal (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0278546.].